2022
DOI: 10.1111/jocd.15230
|View full text |Cite
|
Sign up to set email alerts
|

Hesperetin attenuates UVA‐induced photodamage in human dermal fibroblast cells

Abstract: Background: Ultraviolet A (UVA) radiation causes skin damage. Recently, natural compounds have become an interest to protect skin from UV-induced photodamages. Methods:In this study, we investigated the protective effects of hesperetin, a citrus flavonoid, on UVA-induced oxidative stress, inflammation, apoptosis, and photoaging. Results:Our results showed that hesperetin increased the cell viability, suppressed the intracellular ROS levels, and decreased the expression of MMPs including MMP-1 and MMP-3, pro-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Hesperidin and hesperetin (10 µM) decreased MMP-1 levels in physiologically aged NHDFs by approximately 20%, which is consistent with the study by Santhanam et al [ 21 ], in which hesperidin also decreased the levels of MMP-1 as well as MMP-3 and MMP-9 in UVB-irradiated human fibroblasts. Additionally, the study by Lu et al (2022) showed that pretreatment with hesperetin suppressed the UVA-induced inflammatory response by downregulating MMP-1, IL-6, and cyclooxygenase 2 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hesperidin and hesperetin (10 µM) decreased MMP-1 levels in physiologically aged NHDFs by approximately 20%, which is consistent with the study by Santhanam et al [ 21 ], in which hesperidin also decreased the levels of MMP-1 as well as MMP-3 and MMP-9 in UVB-irradiated human fibroblasts. Additionally, the study by Lu et al (2022) showed that pretreatment with hesperetin suppressed the UVA-induced inflammatory response by downregulating MMP-1, IL-6, and cyclooxygenase 2 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In physiologically aged NHDFs, the level of IL-8 decreased mainly after rhamnose treatment. The fact that hesperidin and hesperetin can regulate oxidative stress and inflammatory activity by down-regulating IL-1β, IL-6, and tumor necrosis factor α (TNF-α), has already been published in a number of studies on skin cells exposed to UVA or UVB radiation [ 30 , 33 , 34 ]. Huang et al (2018) postulated that hesperetin decreased the secretion of IL-6 by infected RAW 264.7 [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Out of these, benzophenone, avobenzone, oxybenzone, sulisobenzone, octisalate, octinoxate, octocrylene, cinoxate, and homosalate are the famous UVA filters 36 . Thus, considering the current escalation in skin cancer cases, there is a greater need to develop newer UVA filters with effective photoprotection and a safer toxicological profile 37 .…”
Section: Discussionmentioning
confidence: 99%
“…All of the above promote skin health [ 11 ]. In human dermal fibroblast cells, hesperetin alleviates UVA-induced damage, including suppressing cell death, reducing oxidative stress, and decreasing the expression of matrix metalloproteinases (MMPs) and pro-inflammatory cytokines [ 12 ]. In rats, topical treatment with hesperetin-based hydrogels protects against UV-induced skin damage [ 13 ].…”
Section: Introductionmentioning
confidence: 99%